A prova prática-oral estruturada é comparável a uma estação do exame clínico objetivo estruturado, na avaliação de habilidades clínicas em estudantes de medicina? Estudo experimental, 2017. - Matos, Flávia Soares de (2018)
Although the objective structured clinical examination (OSCE) is considered golden standard for the assessment of clinical skills, the exam is both expensive and complex. On the other hand, structured oral examinations (SOE) have much simpler application and lower cost. Nonetheless, SOE may have lower validity and reliability. Objective: To compare Medical students’ academic performance and perception in regard of assessing skills through OSCE and SOE. Method: Two tests were designed (OSCE and SOE) to evaluate five obstetrical skills in a mannequin (the first three Leopold maneuvers, fundal height measurement, and fetal heart rate auscultation). The SOE assessed skills separately and the OSCE evaluated the skills after the analysis of a contextualized case. Students of the 4th term of Medical School were distributed into two groups. In the first phase of the study, Group 1 performed SOE, and Group 2, OSCE. Three weeks later, in the second phase, the same tests were applied inversely. Tests were applied by the same teacher, who employed the same checklist in both tests. In the second phase, a survey about students’ perception towards both test types was also applied. The mean score in each question was compared, as well as the final score, concerning the following crossings: test type in each of the two phases; test type regardless of phase; intragroup OSCE and SOE, and scores of the first and second stages, regardless of test type, as well as between groups, regardless of phase. Students’ perception was analyzed according to frequency distribution and grouping of open-ended answers by similarity. Results: 21 students participated in the study: 13 in Group 1, and 8 in Group 2. No difference was found in all the other crossings, except for the scores between phases. As for the intragroup comparison, the final score and the question 2 (fundal height measurement) score were superior in the second phase in both groups. The comparison between mean scores of the first and second phases, regardless of test type, demonstrated that the scores of the second phase were superior in the final score and in all questions, except for the second and third Leopold maneuvers. The scores’ improvement on the second day may be related to the testing effect. Conclusion: the test type did not influence students’ performance. Most candidates preferred the OSCE type.